Analisis Kemampuan Komunikasi Matematis Tertulis Siswa Kelas VII Materi Geometri Bangun Datar ditinjau dari Jenis Kelamin - AM, Alya Riskina; Susanto, Susanto; Abi Suwito (Pendidikan Matematika FKIP Universitas Mataram, 2023)
Written mathematical communication skills are students' ability to express ideas in writing, as well as using images, symbols, and written vocabulary with the aim of conveying correct information according to mathematical rules. This research aims to analyze the written mathematical communication skills of class VII SMP/MTs students on geometric geometric material in terms of gender. This research method uses a qualitative approach with a descriptive research type. The data analysis technique in this research is data triangulation from observation results, mathematical communication ability test results, and interview results. The results of this research show that male students focus more on the final result, but understand the drawings that are made well and have high accuracy in the problem-solving process. Meanwhile, female students provide complete and detailed information about the questions, although they often make mistakes in understanding the questions.